In Silico Study of the Potency of Purple Yam Anthocyanin Compounds (Dioscorea alata L.) As MAO-B and COMT Inhibitors in Parkinson's Disease - Ramadhan, Muhammad Marwan; Utami, Dwi; Yuliani, Sapto (Universitas Ahmad Dahlan, 2024)
The purple yam plant (Dioscorea alata L.) is an economically important staple food for millions of people in tropical and subtropical regions. Dioscorea spp. anthocyanin chemicals have been demonstrated to have antioxidant and neuroprotective properties. The purpose of this study was to explore the potency of anthocyanin compounds in purple yam as antiparkinsonian agents via the monoamine oxidase B (MAO-B) receptor (pdb: 2V5Z) and the catechol-O-methyltransferase (COMT) receptor (pdb: 6I3C) using a molecular docking technique. The study was divided into four stages: (1) pharmacokinetic and Lipinski Rule evaluation, (2) protein (receptor) and ligand preparation, (3) docking method validation, and (4) molecular docking for MAO-B and COMT proteins. Pharmacokinetic prediction and Lipinski rule evaluation revealed that cyanidin, delphinidin, and delphinidin-3-glucoside had an ADMED profile and met Lipinski’s rule. The docking results showed that the binding energy (G) of the compounds cyanidin, delphinidin, and delphinidin-3-glucoside to the MAO-B receptor was lower (-9.50 kcal/mol) than that of the natural ligands ((-4.79 kcal/mol). The Cys172, Leu 171, Ile198, Phe168, Pro104, Trp119 and the 'gatekeeper' residue Ile199 are the amino acids that are majoring involved in MAO-B inhibitors. At the COMT receptor, all the tested compounds had a higher binding energy than native ligands (> -4.79 kcal/mol) except for Cyanidin 3,5-diglucoside (-4.64 kcal/mol). The amino acids Trp143 and Pro174, ensure correct substrate orientation, Mg2+ ions, and cofactor SAM, as well as residues Lys144 and Glu199. In conclusion, this study showed that based on the molecular docking approach, the active compounds of purple yam namely cyanidin, delphinidin, and delphinidin-3-glucoside have the potential to be developed as anti-parkinsonian agents through MAO-B and COMT.